Increased nitric oxide in exhaled air: an early marker of asthma in non-smoking aluminium potroom workers?. Issue 4 (1st April 2000) - Lund, M B; Øksne, P I; Hamre, R; Kongerud, J
Abstract : OBJECTIVES: To study exhaled nitric oxide (NO) as a marker of airway inflammation caused by potroom exposure, hypothesising that ( a ) workers exposed to potroom pollutants would have higher concentrations of NO in expired air than control subjects employed at the same plant but working outside of the potroom atmosphere, and ( b ) that concentrations of exhaled NO in potroom employees might be positively associated with concentrations of fluoride and exposure to dust. METHODS: A study group comprising 186 male subjects (aged 24–63 years), employed in the potrooms of one Norwegian aluminium smelter, and 40 comparable control subjects (aged 25–60 years) recruited from the same plant, were examined by measurements of exhaled and nasal concentrations of NO, spirometry, and a questionnaire on respiratory symptoms as a part of an annual health surveillance programme. Estimates of exposure to fluorides and dust for selected job categories were obtained by means of personal samplers carried by the workers. RESULTS: In the non-smokers, the concentrations of exhaled NO were higher in the potroom workers than in the controls (median (interquartile range) 9.3 (6.2–15.6) v 5.7 (4.6–8.3) ppb, p=0.001). The two groups did not differ in spirometry and asthma-like symptoms. Non-smoking potroom workers with asthma-like symptoms had higher concentrations of exhaled NO than those with no symptoms (median (interquartile range) 21.0 (19.3–41.4) v 8.5 (5.9–12.8) ppb, p=0.001), but had comparable spirometric values. In subjects who smoked, the concentrations of exhaled NO did not differ significantly between potroom workers and controls (median (interquartile range) 4.6 (3.3–8.0) v 4.0 (3.4–5.1) ppb. Exhaled NO was not significantly associated with either duration of employment or routine measurements of dust and fluorides. CONCLUSIONS: Exposure to potroom pollutants is associated with increased concentrations of exhaled NO in non-smoking subjects. Nitric oxide in exhaled air may be an early marker of airway inflammation in aluminium potroom workers.